2016
DOI: 10.1007/s10072-016-2723-6
|View full text |Cite
|
Sign up to set email alerts
|

Screening for intermediate CGG alleles of FMR1 gene in male Iranian patients with Parkinsonism

Abstract: Male carriers of an expansion of CGG alleles (with 55-200 CGG repeats) in the FMR1 gene are affected with Fragile X-associated tremor/ataxia syndrome (FXTAS). On the other hand, individuals with Parkinson's disease (PD) or Parkinsonism spectrum disorders may have some clinical features that overlap with FXTAS. To investigate the possible association between PD and FMR1 expanded alleles, we screened a total of 154 male PD patients and 190 gender- and age-matched healthy control subjects from Iran. Eleven interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…This study highlights intermediate alleles as an opportunity for future research. Prior investigations of intermediate alleles have focused primarily on movement disorders and reproductive function (e.g., Bodega et al, 2005; Debrey et al, 2016; Entezari et al, 2017; Wang et al, 2017) and findings are controversial, as not all reports indicate increased risk in these areas (Toft et al, 2005; Bennett et al, 2010; Kline et al, 2014). To our knowledge, no prior studies have investigated cognitive or linguistic phenotypes relative to intermediate alleles, which is a fruitful avenue of future investigation as intermediate alleles affect a significant proportion of the population (about 1:57 individuals; Cronister et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights intermediate alleles as an opportunity for future research. Prior investigations of intermediate alleles have focused primarily on movement disorders and reproductive function (e.g., Bodega et al, 2005; Debrey et al, 2016; Entezari et al, 2017; Wang et al, 2017) and findings are controversial, as not all reports indicate increased risk in these areas (Toft et al, 2005; Bennett et al, 2010; Kline et al, 2014). To our knowledge, no prior studies have investigated cognitive or linguistic phenotypes relative to intermediate alleles, which is a fruitful avenue of future investigation as intermediate alleles affect a significant proportion of the population (about 1:57 individuals; Cronister et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Another study included 2,362 participants with a prevalence of 5.2% for carriers of the FMR1 gene GZ allele, and GZ alleles were associated with signs of Parkinsonism in men ( Hall et al, 2020 ). These studies suggested that the FMR1 GZ allele might contribute to the etiology of disorders associated with male Parkinsonism ( Entezari et al, 2017 ). A similar study in China, including 360 Chinese patients with Parkinsonism (6.8%) and 295 controls, also supported this result ( Zhang et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…23 In fact, the association has been more often found between FMR1 gray zone alleles (40-54 CGG repeats) and clinical PD in both males and females. [24][25][26][27] In premutation carriers, De Pablo-Fernandez and colleagues 28 reported 2 cases of concomitant FXTAS and PD, both also carrying a lower end CGG repeat number. Our findings expand on the concept that the parkinsonism found in patients with FXTAS is sometimes indistinguishable from the parkinsonism described in the diagnostic criteria of idiopathic PD, 29 and many premutation carriers with FXTAS are still erroneously diagnosed with PD alone.…”
Section: Discussionmentioning
confidence: 99%
“…and a very low prevalence of FMR1 premutation in patients with clinical PD (0%–1%) . In fact, the association has been more often found between FMR1 gray zone alleles (40–54 CGG repeats) and clinical PD in both males and females . In premutation carriers, De Pablo‐Fernandez and colleagues reported 2 cases of concomitant FXTAS and PD, both also carrying a lower end CGG repeat number.…”
Section: Discussionmentioning
confidence: 99%